(untitled) - Nguyễn, Đắc Xuân (Huế, 2013)
Giới thiệu tiểu sử, cuộc đời của vua Hàm Nghi, đặc biệt là thời gian ông bị lưu đày
Keywords: Vietnam,Lịch sữ Việt Nam; History; Nguyen Dynasty, 1802-1883,Triều Nguyễn (1802-1883)